2012
DOI: 10.1095/biolreprod.111.094631
|View full text |Cite
|
Sign up to set email alerts
|

The Chemokine Receptor CCR2 Is Not Required for Successful Initiation of Labor in Mice1

Abstract: Chemokine-driven neutrophil and monocyte recruitment into the uterus and cervix has been proposed to initiate labor. Chemokines that bind CXCR2 direct neutrophil migration and are induced during labor in humans. The chemokine CCL2, induced in the uterus by endocrine and mechanical signals, has been proposed to drive CCR2-dependent monocyte homing to the uterus to contribute to the initiation of labor. However, no direct evidence indicates that chemokines or their receptors play indispensable roles in labor-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 37 publications
2
3
0
Order By: Relevance
“…reported that mice deficient in Ccl2 receptor CCR2 have normal parturition despite reduced monocytes trafficking into the uterus. This study supports the potential importance of myeloid cells in PP uterine involution rather than initiation of term labour [54]. …”
Section: Discussionsupporting
confidence: 87%
“…reported that mice deficient in Ccl2 receptor CCR2 have normal parturition despite reduced monocytes trafficking into the uterus. This study supports the potential importance of myeloid cells in PP uterine involution rather than initiation of term labour [54]. …”
Section: Discussionsupporting
confidence: 87%
“…We observed that intrauterine administration of LPS on day 17 of gestation increased mRNA expression of Ngp in the uterus, placenta, and fetal membranes within 6 h, and that this increased expression was coincident with a large neutrophil influx into the decidua in response to intrauterine LPS treatment, confirming a suggested role for neutrophils in infection-induced PTL. These data contrast to those of Menzies et al (32), who demonstrated that expression of Ngp remains unchanged in laboring compared with nonlaboring mouse uterus and provide further support for the theory that infection-induced PTL and term labor may occur via different mechanisms, with neutrophils playing a specific role in infection-associated PTL (16, 33). …”
Section: Discussionsupporting
confidence: 55%
“…Whether inhibition of a subset of chemokines would be sufficient to reduce decidual immune cell trafficking and suppress inflammation during PTL remains unknown. However, individual chemokine receptor knockout mice do not exhibit a dysfunctional labour phenotype [43], suggesting targeting multiple pathways may be necessary.…”
Section: Discussionmentioning
confidence: 99%